COVID-19 Pandemic Repercussions on the Use and Management of Plastics - Prata, Joana C; Silva, Ana L P; Walker, Tony R; Duarte, Armando C; Rocha-Santos, Teresa (Environmental science & technology, 2020)
Plastics are essential in society as a widely available and inexpensive material. Mismanagement of personal protective equipment (PPE) during the COVID-19 pandemic, with a monthly estimated use of 129 billion face masks and 65 billion gloves globally, is resulting in widespread environmental contamination. This poses a risk to public health as waste is a vector for SARS-CoV-2 virus, which survives up to 3 days on plastics, and there are also broad impacts to ecosystems and organisms. Concerns over the role of reusable plastics as vectors for SARS-CoV-2 virus contributed to the reversal of bans on single-use plastics, highly supported by the plastic industry. While not underestimating the importance of plastics in the prevention of COVID-19 transmission, it is imperative not to undermine recent progress made in the sustainable use of plastics. There is a need to assess alternatives that allow reductions of PPE and reinforce awareness on the proper public use and disposal. Finally, assessment of contamination and impacts of plastics driven by the pandemic will be required once the outbreak ends.